Molecular structural mechanics model for the mechanical properties of microtubules - Chengyuan Wang (Biomechanics and Modeling in Mechanobiology, 2014)
The aim of this paper was to develop a structural mechanics (SM) model for the microtubules (MTs) in cells. The technique enables one to study the configuration effect on the mechanical properties of MTs and enjoys greatly improved computational efficiency as compared with molecular dynamics simulations. The SM model shows that the Young’s modulus has nearly a constant value around 0.83 GPa, whereas the shear modulus, two orders of magnitude lower, varies considerably with the protofilament number NN and helix-start number SS . The dependence of the bending stiffness and persistence length on the MT length and protofilament number NN is also examined and explained based on the continuum mechanics theories. Specifically, the SM model is found to be in good agreement with available simulation and experiment results, showing its robustness in studying the static deformation of MTs and the potential for characterizing the buckling and vibration of MTs as well as the mechanical behaviour of intermediate and actin filaments.